(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To analyze the perceptions of individuals with elimination ostomies regarding the repercussions of participating in a psychoeducational group aimed at strengthening self-care. Method: This qualitative, descriptive, and exploratory study included thirteen individuals with elimination ostomies who participated in a psychoeducational group developed in a specialized stomatherapy clinic affiliated with a public higher education institution in the state of Rio de Janeiro. Data were collected through semi-structured interviews conducted either in person or by telephone, according to participants’ preferences, and were subjected to thematic content analysis. Results: Before joining the group, participants reported experiences marked by negative and traumatic feelings related to the ostomy, difficulties in managing collection devices and accessories, limitations in self-care, and limited psychosocial support. After participation in the psychoeducational group, positive transformations were observed, including increased knowledge, greater confidence in self-care, strengthened autonomy, reframing of the ostomy experience, and a perceived improvement in quality of life. Conclusion: Participation in the psychoeducational group proved to be an effective strategy for strengthening self-care and autonomy among individuals with elimination ostomies by promoting emotional support, exchange of experiences, and access to reliable information, thereby contributing to adaptation to the ostomy condition and to comprehensive care.